Grip Strength Values Stratified by Age, Gender, and Chronic Disease Status in Adults Aged 50 Years and Older. Issue 3 (July 2015) - Yorke, Amy M.; Curtis, Amy B.; Shoemaker, Michael; Vangsnes, Eric
Abstract : Background and Purpose: Grip strength is a measure of overall muscle strength and has been found to be a predictor of disability and mortality. Almost 3 in 4 adults aged 65 years and older have multiple chronic conditions, known as multimorbidity. Normative data for grip strength have commonly been reported on healthy convenience samples that may not accurately represent the population of interest. Grip strength values of US adults, utilizing a nationally representative data set based on the number of chronic diseases, would be beneficial to health care providers who serve adults with multimorbidity. The purpose of this study was to describe grip strength values of adults in the United States, based on gender, age, and the number of chronic diseases. Methods: A cross-sectional analysis was conducted using data collected from adults aged 50 years or older (n = 5877) from the Health and Retirement Study survey administered in 2008. Grip strength values (in kilograms) were determined and stratified on the basis of the number of self-reported chronic diseases (0, 1, 2, ≥3) and stratified by age (decades) and gender. Results: Consistent with previously published values, males demonstrated higher mean hand grip strength than females and grip strength values decreased with age. Adults with multimorbidity demonstrated decreased grip strength as compared with those without chronic conditions (males/females with 0 chronic diseases right grip strength = 44.2/26.8 kg as compared with males/females with 3 or more chronic disease right grip strength = 36.1/21.7 kg). Conclusions: The grip strength values presented can serve as a standard of comparison for the large proportion of adults who have multimorbidity. Clinicians should consider grip strength as a component of a comprehensive physical assessment to identify decreased grip strength and recommend increased physical activity as an appropriate intervention.